Drug and cosmetic safety training for cadres of family welfare program - Tristiana Erawati; Dewi Melani Hariyadi; Noorma Rosita; Widji Soeratri; Tutiek Purwanti; Hadi Poerwono; Marcellino Rudyanto; Helmy Yusuf; Djoko Agus Purwanto; I Nyoman Wijaya (University of Merdeka Malang, 2024)
In order to increase public understanding and awareness regarding the safety use of drugs and cosmetics, the Community Service Team of the Faculty of Pharmacy, Airlangga University has held community service in Jonggrangan Village, Klaten, Central Java. The community service was carried out on July 31, 2023, with approximately 60 family welfare programs or PKK cadres and health cadres participating through training, presentations, and discussions. The activity began with a pre-test, continued with training, a presentation of the material by three experts, and a discussion, then ended with giving a post-test to the participants. The results of the pre and post-test analysis showed that participants' understanding increased. The results of the analysis of the answers to the 15 questions given showed that the increase in participants' understanding ranged from Â 2.13-46.02 percent. The impact of these activities on society. The increase in participants' understanding of each topic is not the same depending on the initial understanding. However, the problem is that the level of public understanding after receiving training is still below 50 percent namely on topics about the stages of using cosmetic products and about drug classification. So it is necessary to deepen the material using other strategies (appropriate methods and media).